Asbabun Nuzul Islamic Education Perspective - Maheningsih, Desi Dwi; Rahmatsyah (Yayasan Sinergi Kawula Muda, 2023)
This research was conducted to analyze asbabun nuzul from the perspective of Islamic education. An in-depth study of asbabun nuzul from the perspective of Islamic education is rarely carried out in a learning process, moreover it will analyze the educational values contained in the asbabun nuzul. This study uses a library research approach (library research). The results of this study are asbabun nuzul as an event that causes the decline of one or several verses of the Qur'an, or an event that can be used as a legal guide regarding the revelation of a verse. How to find out asbabun nuzul through authentic history, namely history based on the Prophet Muhammad SAW. Asbabun nuzul consists of several types which in general are asbabun nuzul based on responses to events and asbabun nuzul based on questions to the Prophet SAW, the benefits and educational values in asbabun nuzul broadly teach humans to be able to take lessons from the cause of the incident.